(untitled) (Research, Society and Development, 2020)
Objective: To analyze from the literature the relationship of coffee consumption as a risk factor for the development of peptic ulcers. Method: This article is an integrative review carried out in the Web of Science and PubMed databases, and the Journal Portal of the Coordination for the Improvement of Higher Education Personnel (CAPES) of the Ministry of Education of Brazil (MEC), with 8 articles published between 2000 and 2020 being selected according to criteria of inclusion and exclusion. Results: Cross-sectional studies (50%) prevailed, followed by prospective cohort studies (25%) and finally by a longitudinal study (12.5%) and a systematic review (12.5%), with each original article written around research in a different country. Conclusion: From the data obtained in the selected articles, it is suggested that coffee consumption is not, after all, a risk factor for the development of peptic ulcers, but the need for more research directed at this theme becomes evident.